2021
DOI: 10.1186/s12859-021-04128-1
|View full text |Cite
|
Sign up to set email alerts
|

Paired-end small RNA sequencing reveals a possible overestimation in the isomiR sequence repertoire previously reported from conventional single read data analysis

Abstract: Background Next generation sequencing has allowed the discovery of miRNA isoforms, termed isomiRs. Some isomiRs are derived from imprecise processing of pre-miRNA precursors, leading to length variants. Additional variability is introduced by non-templated addition of bases at the ends or editing of internal bases, resulting in base differences relative to the template DNA sequence. We hypothesized that some component of the isomiR variation reported so far could be due to systematic technical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In the literature, there is a concern that sequencing and/or mapping artefacts may result in an overrepresentation of isomiRs [30]. However, previous studies have shown that isomiRs represent actual molecules rather than sequencing artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is a concern that sequencing and/or mapping artefacts may result in an overrepresentation of isomiRs [30]. However, previous studies have shown that isomiRs represent actual molecules rather than sequencing artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR technology is still considered the gold standard for validation of findings made during high-throughput analyses; however, it has inherent biological and experimental limitations for exosomal miRNA studies, which include: (1) The discovery of tumor miRNA panels specific to a tumor exosome remains limited to known or selected miRNAs (which can be multiplexed for up to 700 miRNAs using TaqMan card arrays) rather than global unbiased NGS analyses. In this fashion it does not allow discovery of IsomiR (i.e., miRNA variants of the same miRNA, which can differ in sequence and/or length composition and will bind to different mRNA targets than the original miRNA sequence [ 306 ]) expression ratio differences for a specific miRNA in exosome sub-populations. The study of isomiRs is relevant in cancer, as their expression ratio has been shown to be affected by and can elicit changes in tumor cell migration and invasion [ 307 ].…”
Section: Exosomes: a Source Of Tumor Biomarkersmentioning
confidence: 99%
“…NGS offers a great opportunity to specifically and sensitively detect isomiRs. However, the analysis of isomiRs remains a challenge, due to the limited number of specific tools available to analyze their expression levels in sequencing experiments and the lack of comparison among them [47] as well as the possible overestimation of isomiRs detected [99].…”
Section: Isomirs Detection and Quantificationmentioning
confidence: 99%